2015
DOI: 10.1186/s12883-015-0277-5
|View full text |Cite
|
Sign up to set email alerts
|

Vim thalamotomy in a patient with Holmes’ tremor and palatal tremor - Pathophysiological considerations

Abstract: BackgroundWe peformed a ventral intermediate nucleus (Vim) thalamotomy in a patient with Holmes’ tremor and palatal tremor. The frequencies of these movement disorders were 4 Hz and 3 Hz, respectively. Vim thalamotomy stopped the Holmes’ tremor but not the palatal tremor. Our observations suggest different mechanisms for these two involuntary movements.Case presentationA 57-arm 11 months after a pontine hemorrhage. Transoral carotid ultrasonography revealed periodic motion of her posterior pharyngeal wall with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…We found that surgical lesions or DBS sites that improve Holmes tremor are part of the same connected brain circuit as the lesion that caused the tremor in the first place. Although potentially counterintuitive, this finding may align with pathological oscillations recorded in Holmes tremor patients . The first lesion could unbalance the circuit, setting up a pathological oscillation, and a second hit to this same circuit could break this oscillation, providing therapeutic benefit.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found that surgical lesions or DBS sites that improve Holmes tremor are part of the same connected brain circuit as the lesion that caused the tremor in the first place. Although potentially counterintuitive, this finding may align with pathological oscillations recorded in Holmes tremor patients . The first lesion could unbalance the circuit, setting up a pathological oscillation, and a second hit to this same circuit could break this oscillation, providing therapeutic benefit.…”
Section: Discussionsupporting
confidence: 84%
“…Although potentially counterintuitive, this finding may align with pathological oscillations recorded in Holmes tremor patients. 35 The first lesion could unbalance the circuit, setting up a pathological oscillation, and a second hit to this same circuit could break this oscillation, providing therapeutic benefit. If the therapeutic lesion must be part of the same circuit as the causative lesion, none of our current DBS targets would be expected to improve Holmes tremor in all cases.…”
mentioning
confidence: 99%
“…Rare tremor syndromes, such as DBS-resistant ET or poststroke tremor, may respond favorably to thalamotomy. 15,16 In our series, neuropathic and cerebellar tremor, respectively, were treated successfully, although the latter patient had continued hand dysfunction as a result of comorbid dysmetria, which is common in cerebellar tremor. 2 Thus clear expectations should be set that comorbid preoperative cerebellar signs will not necessarily improve along with tremor, which may temper enthusiasm depending on the source of disability.…”
Section: Discussionmentioning
confidence: 67%
“…Rare tremor syndromes, such as DBS‐resistant ET or poststroke tremor, may respond favorably to thalamotomy . In our series, neuropathic and cerebellar tremor, respectively, were treated successfully, although the latter patient had continued hand dysfunction as a result of comorbid dysmetria, which is common in cerebellar tremor .…”
Section: Discussionmentioning
confidence: 72%
“…The surgical perforation of the tympanic membrane and the excision of the LVP, TVP and tensor tympani muscle did not provide any obvious benefit [ 82 ]. A thalamotomy also did not provide benefit in a patient with both PT and Holmes’ tremor [ 87 ]. The bilateral deep brain stimulation of the red nucleus did not reduce OPT in one patient [ 28 ].…”
Section: Treatmentmentioning
confidence: 99%